Meaning of aging for caregivers of senile elderly people - Sara Ingrid de Rezende Ferreira; Elen Ferraz Teston; Sonia Silva Marcon; Bianca Cristina Ciccone Giacon-Arruda; Juliete Bispo dos Santos Mandu; Josiel Elisandro Werle; Sueli Aparecida Frari Galera (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to understand the meaning of aging for caregivers of senile elderly people. Methods: qualitative study carried out with 12 caregivers of elderly people registered in the Home Care Service, adopting the Explanatory Model of Kleinman's Disease as a theoretical framework. Data were collected from April to June 2019, through semi-structured, audio-recorded interviews, carried out at home and submitted to content analysis. Results: taking care of senile elderly people triggers reflections on aging that sometimes lead to a new meaning of this process, besides stimulating the recognition of the factors that influence it, with emphasis on the life history, occupation and deleterious behaviors adopted throughout life. Final Considerations: the care experience influences the meaning attributed to aging, favoring: the identification of modifiable and non-modifiable aspects and behaviors that make it healthy; reflection on aging itself, with a new meaning of habits and behaviors to be adopted.